A Study on Syntactic and Semantic Features of Commissers in English versus Vietnamese - Lê Văn Bá (2005)
This study investigates the syntactic, semantic and pragmatic features of commissive speech acts (CSAs) in English and Vietnamese. The study focuses on the syntactic and semantic representation of CSAs in English and Vietnamese and the similaries and differences between people from English speaking countries (CSAs) and the Vietnamese in ways of performing CSAs. To discuss the issues thoroughly we employ data from novels, short stories, and film scripts. We also take into account social parameters like social distance and social power to determine how they affect the way people perform CSAs in ESCs and in Vietnam. Some typical strategies used in performing CSAs in English and Vietnamese are presented in the light of the politeness theory by Brown and Levinson. Also, implications are put forward for the teaching and learning of English for the Vietnamese learners concerning speech acts in general and CSAs in particular.